Covering and explaining conflict in Civil society/ edited by Nalini Rajdhan (New Delhi)
Key Features 1. Accessible Language: The volume has been written by current and former journalists, and the language is very journalistic, i.e. easy to follow and very accessible by the society. 2. Pertinent to Current Affairs: The volume deals with topics such as the Arab Spring, Corruptions and scandals of Central governments, atrocities against dalits and social media. 3. Healthy mix of Authors: The authors are journalists, editors and academics. They include experience of reporting in South Asia, Africa and the Middle-east. This book is much benefitted by the exposure these authors have experienced. About the Book: Covering and Explaining Conflict in Civil Society Covering and Explaining Conflict in Civil Society is a collection of essays that highlights issues of ethics specifically in journalism of conflict. The media takes an active interest in reporting cases of conflict as political unrest has a direct and immediate impact on peoples lives. In the first part, this volume presents four such reportages; one each from Libya, Pakistan, Turkey and Khairlanji (India). Devoted to reportage, these case studies raise an important question: How far can a reporter prescribe and opine in her reportage? The authors explain, by their own example, the need for a journalist to be aware of this question during live reportage. The second part of this volume is a critical look at the contemporary media scene in India. The authors draw our attention to the vibrant civil society that shook the administration when allegations of corruption cropped up. Citing instances of corruption within the media, the essays delineate the conflict between vested interest and ethics in journalism. In the concluding part, the authors focus on social media, as a new medium of civil society, playing an active role in the reportage of conflict-through clicks and shares. The essays here provoke the reader to ask if journalistic ethics do find a place in social media at all! Presenting case-studi
Keywords: "Conflict and conflict resolution, Journalism, Rajan, Nal"